Application of the Team Games Tournament Learning Model to Improve Gymnastics Learning Outcomes in High School Students - Rio Amadeo Pratama; Wening Nugrahaeni; Firman Septiadi (Universitas Riau, 2025)
This study aims to improve the learning outcomes and enthusiasm of students in Class XI IPA 1 at SMA Negeri 4 in Sukabumi City regarding the back roll floor exercise, for which their performance was previously low. The method used was Classroom Action Research (CAR) with a quantitative approach. The sample was selected using purposive sampling. Data collection was conducted through pre- and post-tests to measure the impact of implementing the Team Games Tournament (TGT) learning model. The results showed a significant improvement, with the students’ average score rising from 71 (the “Insufficient” category, below the minimum passing score) on the pre-test to 84, with a mastery rate of 94% (the “Excellent” category) on the post-test. In conclusion, the implementation of the TGT learning model is effective in improving student learning outcomes. Based on these results, it is recommended that the school organize workshops for teachers to enhance their competence in developing lesson plans tailored to student characteristics.